2014
DOI: 10.1007/s00436-014-3995-5
|View full text |Cite
|
Sign up to set email alerts
|

Description, molecular characterization, and patterns of distribution of a widespread New World avian malaria parasite (Haemosporida: Plasmodiidae), Plasmodium (Novyella) homopolare sp. nov.

Abstract: Plasmodium (Novyella) homopolare, a newly described Plasmodium species, was found in a wide range of Passeriformes species in California, USA, and Colombia. This parasite infected more than 20% of the sampled bird community (N = 399) in California and was found in 3.6% of birds sampled (N = 493) in Colombia. Thus far, it has been confirmed in North and South America where it is present in numerous species of migratory and resident birds from six families. Based on 100% matches, or near-100% matches (i.e., ≤2-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 49 publications
2
38
0
Order By: Relevance
“…(N.) homopolare lineage BAEBIC02 included identical sequences from 10 individuals belonging to three families of Passeriformes. This parasite lineage has been recorded previously in eight bird species from North America [40]. In contrast, P. (N.) unalis lineage TFUS06 included identical sequences from six individuals and appears to preferentially infect only members of the Turdidae family, particularly T. fuscater.…”
Section: Phylogenetic Analysis Of Cytochrome B Lineagesmentioning
confidence: 55%
See 4 more Smart Citations
“…(N.) homopolare lineage BAEBIC02 included identical sequences from 10 individuals belonging to three families of Passeriformes. This parasite lineage has been recorded previously in eight bird species from North America [40]. In contrast, P. (N.) unalis lineage TFUS06 included identical sequences from six individuals and appears to preferentially infect only members of the Turdidae family, particularly T. fuscater.…”
Section: Phylogenetic Analysis Of Cytochrome B Lineagesmentioning
confidence: 55%
“…The Neotropical region offers a great opportunity for research on avian haemoparasites; this study found new host-parasite relationships, most likely due to high avian diversity associated with the uplift of the Andes, and the scarce number of studies on this topic in the Andean region [7][8][9][10][11][12][13][14][15]40,54,55]. An increasing number of lineages from avian Haemosporida have been recorded in the last decade around the world.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations